Ultrasound findings provide clues to investigate founder mutations expressed as runs of homozygosity in chromosomal microarray studies. (19th January 2018) - Daum, Hagit; Lerer, Israela; Frumkin, Ayala; Rosenak, Daniel; Yanai, Nili; Porat, Shay; Yagel, Simcha; Meiner, Vardiella
Abstract : What's already known about this topic? ROH mapping is a diagnostic tool in the investigation of genetic disease within consanguineous families; however, in isolated populations, no consanguinity is required as a result of long‐term ancestral isolation. What does this study add? Known founder mutations within isolated populations together with SNP array in the prenatal testing, and with corresponding ultrasound abnormalities assist in achieving an accurate prenatal diagnosis in a tight schedule. Abstract: Objectives: Chromosomal microarray analysis is effectively applied prenatally to detect copy number changes. Single nucleotide polymorphism (SNP) probes included in the microarray platform can detect regions of excessive homozygosity and identical‐by‐descent genomic stretches. The utility of the latter as part of prenatal diagnosis is not well established. Recessive founder mutations are well recognized within distinct ethnic groups. Combining these data with prenatal sonography provides accurate focused molecular diagnoses quickly. We aimed to evaluate the application of this approach in expectant families presenting to our unit. Methods: Three unrelated gravidae presenting with specific fetal sonographic findings: (1) ventriculomegaly with encephalocele; (2) severe polyhydramnion; and (3) enlarged echogenic kidneys, underwent amniocentesis for chromosomal microarray analysis, and genome‐wide human SNP array was used to analyze DNA from amniocytes. The Genomic Oligoarray and SNP array evaluation tool v3.0© was used to detect recessive loci associated with the reported clinical findings. Candidate genes were further interrogated using the Israeli National Genetic Database (INGD) and specifically searching and identifying a corresponding founder mutation within the defined ethnic group. Results: Three fetuses from 3 distinct nuclear families in which the parents shared a similar ethnicity (either Ashkenazi or Bukharan Jews) albeit no reported consanguinity were assessed. We found no copy number changes; however, by evaluating regions of homozygosity, we were able to reveal relevant candidate gene for the specific phenotype for each fetus. Using the INGD led to targeted testing of a specific homozygous fetal mutation for which parents were found to be carriers. In the fetus with ventriculomegaly with encephalocele c.1167dupA mutation in the FKTN gene, in the fetus with severe polyhydramnion c.167ins6[TTTCCC] mutation in the BSND gene, and in the fetus with enlarged echogenic kidneys, c.3761_3762delCCinsG in the PKHD1 gene were identified. Conclusions: A tripartite approach integrating sonographic pathology with regions of excessive homozygosity data and INGD‐based founder mutation repository yields a comprehensive streamlined approach to provide accurate genetic diagnosis and counselling within the time constraints of an ongoing pregnancy.